2019
DOI: 10.3390/ijms20225559
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Activity of a 5-Aminopyrazole Derivative Lead Compound (BC-7) and Potential Synergistic Cytotoxicity with Cisplatin against Human Cervical Cancer Cells

Abstract: The use of some very well-known chemotherapeutic agents, such as cisplatin, is limited by toxicity in normal tissues and the development of drug resistance. In order to address drug resistance and the side-effects of anti-cancer agents, recent research has focused on finding novel combinations of anti-cancer agents with non-overlapping mechanisms of action. The cytotoxic effect of the synthetic 5-aminopyrazole derivative N-[[3-(4-bromophenyl)-1H-pyrazol-5-yl]-carbamothioyl]-4-chloro-benzamide (BC-7) was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The anticancer mechanism of silibinin was varied, including cell proliferation, invasion, and apoptosis. This work showed that silibinin was different from other anticancer drugs which were only cytotoxicity to cell death (Swanepoel et al, 2019). It also prevented the protein phosphorylation of MEK1/2 and ERK1/2 through inhibiting TMEM16A expression and finally arrested the cancer cells in G0/G1.…”
Section: Discussionmentioning
confidence: 86%
“…The anticancer mechanism of silibinin was varied, including cell proliferation, invasion, and apoptosis. This work showed that silibinin was different from other anticancer drugs which were only cytotoxicity to cell death (Swanepoel et al, 2019). It also prevented the protein phosphorylation of MEK1/2 and ERK1/2 through inhibiting TMEM16A expression and finally arrested the cancer cells in G0/G1.…”
Section: Discussionmentioning
confidence: 86%
“…Assays were conducted in 96-well plates and 9 sites per well were imaged, covering an area of approximately 63.5% of the total well area. The number of cells imaged was dependent on the cytotoxicity of the treatment [ 105 ].…”
Section: Methodsmentioning
confidence: 99%
“…A very good example of its effectiveness has been shown when combined with Clarithromycin to suppress the invasion and proliferation of ovarian cancer cells, which elevates apoptotic cell death by increasing the production of reactive oxygen species (ROS) [43]. A combination of CP and a 5-aminopyrazole derivative lead compound (BC-7) stimulates M-phase arrest and prevents the proliferation of cervical cancer cells [44]. It is worth mentioning that CP and docetaxel (DOX) can be administered prior to surgery to increase the survival resection rate, reduce intraoperative blood loss, and extend the patient's survival time.…”
Section: Cisplatin In Cancer Therapymentioning
confidence: 99%